The association between duration of breastfeeding and atopy in children with or without family history of atopic disease - Riana Novy; Budi Setiabudiawan; Cissy B. Kartasasmita (Indonesian Pediatric Society Publishing House, 2007)
Background Atopic diseases (AD) are the most common chronic diseases in childhood, and their incidence has a tendency to increase recently. Tendency to have atopy could be triggered by many factors originated in early life, including time of breastfeeding cessation. Objective To determine the association between exclusive and duration of breastfeeding and atopy in children with or without family history of atopic disease. Methods This was an observational clinical epidemiology study performed at Babakansari, Padasuka, Garuda Primary Health Care Center in Bandung from January to March 2006. One hundred fifty of 749 children were randomized from group with and without family history of AD. They underwent skin prick tests and total serum IgE level analysis. Atopy was defined as a positive skin prick test to any of the eight allergens tested. History of exclusive and duration of breastfeeding was obtained from their parents. Significance tests for contingency tables were on the basis of x 2 test for association odds ratio with 95% confidence interval. Results Atopy was found in 28.2% of children, of whom 32.4% with and 23.9% without family history of AD. Children exclusively breastfed exhibited a reduced risk of atopy (5.8% v 35.3%, OR=0.11, 95%CI= 0.03;0.34, P<0.001). The difference of atopy was strongly significant between children who had exclusive breastfeeding and those without exclusive breastfeeding whether or not the subjects had family history of AD (P<0.001). There was a highly significant risk reduction for atopy related to prolonged breastfeeding (=6 months) (OR=0.37, 95%CI = 0.19 to 0.72, P=0.001). The difference of atopy was strongly significant between children who had prolonged breastfeeding and short breastfeeding duration whether or not the subjects had family history of AD (P<0.001) Conclusions Exclusive and prolonged breastfeeding decrease atopy in children with as well as without family history of AD.